To biopsy or not to biopsy? Outcomes following stereotactic body radiotherapy (SBRT) for biopsy‐confirmed versus radiologically‐diagnosed primary lung cancer in a single Australian institution. Issue 3 (29th June 2021) - Koh, Tze Lui; Ong, Wee Loon; Farrugia, Briana; Leong, Tracy; Lapuz, Carminia; Lim, Adeline
Abstract: Introduction: Obtaining tissue diagnosis for lung cancer can sometimes be difficult and unsafe. We evaluated outcomes of biopsy‐confirmed versus radiologically‐diagnosed lung cancer treated with stereotactic body radiotherapy (SBRT). Methods: A single‐institutional retrospective cohort of lung cancer patients treated with SBRT between February 2014 and October 2018. Outcomes of interest were: local failure (LF), distant failure (DF), and overall survival (OS). Probability of LF, DF, and OS were estimated using the Kaplan–Meier method. Differences in outcomes between biopsy‐confirmed versus radiologically‐diagnosed lung cancer were evaluated using the log‐rank test. Results: Sixty‐five lung lesions in 61 patients were treated with SBRT. Mean age was 75.6 years. Twenty‐seven patients (44.3%) were ECOG 2–3. Thirty‐nine patients (64%) were radiologically‐diagnosed. There were five cases of LF observed at median of 12.8 months post‐SBRT and 12‐month LF‐free survival was 96% (95% CI, 86–99%), with no differences between groups ( p = 0.1). Sixteen patients developed DF, with 12‐month DF‐free survival of 84% (95% CI, 71–91%), and no difference between groups ( p = 0.06). Sixteen deaths were reported at a median of 12.5 months post‐SBRT, with 12‐month OS of 85% (95% CI, 73–92%), and no differences between study groups ( p = 0.5). No grade 3 toxicities were reported. Conclusion: The oncological outcomes were similar in patients with early lung cancer treated with SBRT with or without biopsy‐confirmation. In situations where tissue diagnosis is not feasible or unsafe, it is not unreasonable to offer SBRT based on clinical and radiological suspicion following multidisciplinary discussions. Abstract : Establishing a definite diagnosis of lung lesions can be difficult. This study reveals similar oncological outcomes between patients with early primary lung cancer treated with stereotactic body radiotherapy (SBRT) with or without biopsy‐confirmation. However, clinicians should strive to obtain tissue diagnoses wherever safe, to ensure that the most diagnosis‐appropriate treatment recommendations are made.